Journalists' understanding of COVID-19 coverage in Medan, Indonesia - muhammad thariq . (Jurnal Studi Komunikasi, 2024)
The background of this research highlights how the COVID-19 pandemic has brought significant changes to various aspects of life, including journalism. In the city of Medan, journalists face unique challenges in covering pandemic-related news and must quickly adapt to rapid technological changes. The purpose of this study is to assess the level of understanding of journalists in Medan City regarding technological changes in COVID-19 coverage. The research method used was conducted through Purposive Sampling interviews with 60 journalists in Medan City focusing on their experiences in reporting about the pandemic and how they used technology in their work. The results found by the researchers during the conduct of this study showed that 90% of journalists from the number of informants in Medan used their smartphones as the main tool of news coverage during the COVID-19 pandemic. 80% of them stated that this technology facilitates communication and collaboration with colleagues and resource persons, allowing for rapid adaptation to technological changes during crises. The conclusion of this study shows that 90% of journalists in Medan used smartphones as their main tool during the COVID-19 pandemic. This technology makes communication and collaboration easier, allowing journalists to adapt quickly to technological changes in times of crisis. The study is expected to contribute to a further understanding of the challenges and adaptations of journalists during crises such as a pandemic.